The Importance of Experience in Enhancing Proof of Administrative cases: A Comparative Study) - Hamid Abdulaali Al Tamimi, Lect. Dr. Abdulaali (Basra studies journal, 2025)
Expertise is no longer the exclusive evidence in the judicial procedure, as other evidence such as inspection and testimony remain available to the administrative judge. However, resorting to it still rare in practice, despite its simplicity and speed. The importance of studying expertise lies in its legal framework and in its vital role, which is not limited to strengthening evidence, but extends to providing assistance and assistance to the judge. Since expertise plays a pivotal role in many lawsuits, as it is an essential and fundamental evidence on which the resolution of the dispute and the adjudication of the case depend, judges often face cases that include facts that exceed the limits of their knowledge and awareness. Here the true importance of expertise emerges in interpreting and analyzing these facts in an accurate scientific manner. The specialized expert submits a detailed report to the judge, which helps him make a fair decision based on the findings of the expertise.